PELAKSANAAN TUGAS ORDER TAKER DEPARTEMENT HOUSEKEEPING DI NAGOYA MANSION HOTEL & RESIDENCE BATAM - Pardede, Putra Sarmika Antonius; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Nagoya Mansion Hotel & Residence Batam is a hotel located in the middle of batam city. This hotel became one of the hotels that have the tallest building in batam city. Nagoya Mansion Hotel & Residence Batam is one of the best hotels in downtown batam. The hotel has two adjoining buildings. Where the first building is named Tower A and the second is named Tower B, each tower has the same number of floors and the same building form. Nagoya Mansion Hotel & Residence Batam is located on Jalan Kampung Utama, Jl. Imam Bonjol No.1, Lubuk Baja Kota, Batam City, Batam City, Riau Islands. The position of Nagoya Mansion Hotel & Residence Batam is right in the middle of batam city, so it will not be far from the center of the batam in batam city. Nagoya Mansion Hotel & Residence has twenty-two floors where the apartments start from the fifth to sixteenth floors, and for the hotel chain starting from seventeen to twenty-two floors. From the results of research authors who talked about the hotel services, especially in department housekeeping. Can be said that this hotel can be one of the many hotels inhabited by guests who are in the city batam. With the position of the hotel with the hub of batam city center, it can be seen hotel guests who stay is for business and for leisure. Keyword: Implementation of Order Taker Task.